The Relationship between Maternal Knowledge of the "Isi Piringku" Program and the Nutritional Status and Development of Toddlers at the Posyandu - Arina Izzatun Jannah; Tina Muzaenah (Indonesian Journal of Global Health Research, 2025)
Toddlers are in the "Golden Age Period," where their growth and development are highly influenced by nutritional intake. Mothers play a key role in planning daily meals that meet the nutritional needs of their children, with the government’s "Isi Piringku" program serving as a guideline for meal planning. This study aims to analyze the relationship between mothers' knowledge of the Isi Piringku program and the nutritional status and development of toddlers at Posyandu in Sumbang Village. This cross-sectional study employed an analytical observational approach. The sample size was calculated using the Slovin formula, with cluster random sampling as the sampling technique. The Gamma correlation test was used to analyze the relationship between variables. The study found a significant relationship between mothers' knowledge of Isi Piringku and toddlers' nutritional status (p-value = 0.000; r = 0.818). Additionally, there was a strong correlation between mothers' knowledge and toddler development (p-value = 0.000; r = 0.717). Mothers' knowledge of the Isi Piringku program is significantly related to the nutritional status and development of toddlers at Posyandu in Sumbang Village.